The Nodovenous Shunt and Reduction Surgery for Post-Filarial Lymphedema—Surgical Technique and Clinical Outcomes - Victor, Jonathan; Stephen, Tovia; Guin, Devajyoti; Victor, Joseph (Indian Journal of Plastic Surgery, 2021)
Background Most of the patients in our Indian setting present with grade 4 lymphedema in which no other surgical option is available and in these debilitating cases the nodovenous shunt followed by reduction surgery provides acceptable outcomes. We would like to describe the surgical technique used for the nodovenous shunt procedure and debulking surgery done in post-filarial lymphedema and share our experience with clinical outcomes.Materials and Methods This was a descriptive study. The study period was from 2010 to 2019. Patient records were reviewed retrospectively, and the data was analyzed. All patients with post-filarial lymphedema, operated by two surgeons, were studied. The surgical technique was described.Results In the study period, 16 patients with lymphedema were treated surgically. The number of procedures done was 32. In 14 of them nodovenous shunt followed by debulking surgery was done. Two of the patients with post-filarial lymphedema had multiple nodules following secondary skin changes and in them sculpting surgery was done following the nodovenous shunt. Most of the patients presented with grade 4 lymphedema. In all the patients there was significant (>5 cm) reduction in limb circumference postoperatively.Conclusion Nodovenous shunt followed by reduction surgery for lymphedema is a reliable surgical option to reduce disease morbidity in patients with post-filarial lymphedema.
Keywords: filarial lymphedema; lymphatic filariasis; nodovenous shunt